SUATU TINJAUAN TERHADAP PENERAPAN DISSENTING OPINION DALAM PENYELESAIAN PERKARA KEPAILITAN - ABDUL RIFAI (University of North Sumatera, 2013)
Abstrak : Inspection system at the level of the Court, including the Commercial Court to condition the three judges who examine a bankruptcy case. Changes in the condition of Indonesian justice especially by issuing Law No.. 35 of 1999 on the Amendment of the Act No.. 14 Year 1970 on Basic Provisions of the Judicial Authority contributes dissent judges who examine cases including the case of a bankruptcy in the case verdict. Differences of opinion in deciding a case is called by the term